URGENSI BERAGAMA DI ERA PERKEMBANGAN IPTEK (ANALISIS PEMIKIRAN M. NURUDDIN DALAM VIDEO YOUTUBE KAIFA CHANNEL) - Reo Chandrika; Jeni Lovita (Pojok Publisher, 2025)
This research aims to analyze M. Nuruddin's views regarding the role of religion in the context of current advances in science and technology (IPTEK) in his video recording on the Kaifa YouTube channel with the title